2013
DOI: 10.1016/j.nurpra.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Sliding Scale vs. Basal/Bolus Insulin Protocols

Abstract: The purpose was to assess the differences between subcutaneous basal/bolus and sliding scale insulin protocols in patients admitted with type 2 diabetes on non-critical care units. Methods A retrospective review of electronic medical records was conducted on a convenience sample of inpatients in a central-city teaching hospital. Results The findings were that basal/bolus protocols achieved American Diabetes Association glycemic targets on fasting, mean, and discharge blood glucoses. Conclusions This study prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…In other words, there were no statistical differences between groups as related to age, gender and length of stay which was similar to other literature reviews of Rymaszewski &Breakwell, 2013, andUmpierrez et al, 2013. In comparison of the average blood glucose of the two groups, this study revealed that the SSI group showed a lower average blood glucose than the BBI group. This is contrary to several studies which demonstrated the clinical benefits (Fahim et al, 2015) and better glycemic control of using BBI over SSI (Roberts & Godbole, 2015;Rymaszewski & Breakwell, 2013;Umpierrez et al, 2013). In fact, Umpierrez et al, 2013 found that SSI patients who missed their insulin doses or received higher medication doses had more statistically significant hyperglycemic events (Umpierrez et al, 2013).…”
Section: Average Blood Glucosesupporting
confidence: 90%
See 3 more Smart Citations
“…In other words, there were no statistical differences between groups as related to age, gender and length of stay which was similar to other literature reviews of Rymaszewski &Breakwell, 2013, andUmpierrez et al, 2013. In comparison of the average blood glucose of the two groups, this study revealed that the SSI group showed a lower average blood glucose than the BBI group. This is contrary to several studies which demonstrated the clinical benefits (Fahim et al, 2015) and better glycemic control of using BBI over SSI (Roberts & Godbole, 2015;Rymaszewski & Breakwell, 2013;Umpierrez et al, 2013). In fact, Umpierrez et al, 2013 found that SSI patients who missed their insulin doses or received higher medication doses had more statistically significant hyperglycemic events (Umpierrez et al, 2013).…”
Section: Average Blood Glucosesupporting
confidence: 90%
“…Although the researcher was not able to determine the hypoglycemic events in this study, Rymaszewski and Breakwell (2013) Elliott et al (2016) found that it is also important to use HbA1c as platform targets to understand higher hypoglycemic event rates because patients might present with no symptoms, patients and nurses might not notice no symptoms, and they might underreport events. The study outcomes, which were consistent with Elliott et al's (2016) findings, indicated that the retrospective chart review could likely underestimate the real incidence of glycemic control, as compared with the prospective study.…”
Section: Average Blood Glucosementioning
confidence: 95%
See 2 more Smart Citations
“…Meskipun demikian, pada kondisi tertentu sasaran kendali glikemik pada A1C di bawah 7,5%. Terapi insulin merupakan metode yang direkomendasikan untuk dapat mengontrol kadar glikemik pada pasien diabetes dan memiliki nilai prediktif yang kuat untuk komplikasi diabetes (CDC, 2007;ADA, 2010;Rymaszewski & Breakwell, 2013).…”
Section: Pendahuluanunclassified